Assessment of the straightness condition of the overhead crane trestle in a steel structure - Kubicki, Rafał; Mrówczyńska, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents a geodetic method of assessing the straightness condition of an overhead crane trestle made in a steel structure. In particular, control measurements of overhead cranes and a course of action aimed at determining deviations of beam axles from design assumptions, as well as deviations from the planned range of the axles of the overhead crane rails have been discussed. The measurements were made using classic geodetic methods, and two methods - graphical and analytical - were used to develop the results. The graphic interpretation of the obtained results is also presented.
Keywords: overhead crane trestle; straightness; control measurements of overhead cranes